When amiodarone-induced thyroiditis meets cardiomyopathy with excessive trabeculation: a case report - Gašparini, Dora; Raljević, Damir; Pehar-Pejčinović, Vesna; Klarica Gembić, Tihana; Peršić, Viktor; Turk Wensveen, Tamara (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Amiodarone is a potent antiarrhythmic medication used to treat life-threatening ventricular arrhythmias; however, its well-established adverse effect is a thyroid disorder. Amiodarone-induced thyroiditis (AIT), a clinical entity involving two types with different etiopathology and treatment approaches, may occur at the beginning or even several years after amiodarone treatment discontinuation. The toxicity profile of amiodarone becomes especially important in young patients with lifelong cardiac disorders, which are often refractory to other antiarrhythmic drugs. Herein, we report the first case of non-sustained ventricular tachycardia (NSVT), an unusual presentation of type II AIT, in a young male patient who was previously diagnosed with left ventricular cardiomyopathy with excessive trabeculation. Case report: A 36-year-old male nonathlete presented with tiredness during regular follow-up. Continuous electrocardiographic monitoring (cECG) revealed NSVT, whereas echocardiography and cardiac magnetic resonance imaging detected discrete structural and functional changes that could not fully explain the observed cECG report. Conversely, an unmeasurably low thyrotropin level on admission and previous exposure to amiodarone pointed the diagnostic pathway in the direction of the thyroid gland. Elevated free thyroxine and undetectable autoantibody titers with unremarkable sonographic findings raised clinical suspicion of type II AIT. Scintigraphic imaging with 99m Tc-2-methoxyisobutylisonitrile (sestamibi) revealed decreased thyroid uptake; hence, prednisone was introduced for treatment. Clear improvements in both biochemical and electrocardiographic parameters were observed after immunomodulatory treatment of type II AIT in this young patient with cardiomyopathy and excessive trabeculation. Conclusion: Treatment of reversible causes of cardiac rhythm abnormalities such as type II AIT should be considered before choosing other treatment modalities, particularly in patients with structural cardiac disorders. The importance of a multidisciplinary approach in complex cases such as the one reported, thus, cannot be emphasized enough.